Entropic solvation force between surfaces modified by grafted chains: a density functional approach - Pizio, S.; Sokołowski, O. (Condensed Matter Physics, 2010)
The behavior of a hard sphere fluid in slit-like pores with walls modified by grafted chain molecules composed of hard sphere segments is studied using density functional theory. The chains are grafted to opposite walls via terminating segments forming pillars. The effects of confinement and of "chemical" modification of pore walls on the entropic solvation force are investigated in detail. We observe that in the absence of adsorbed fluid the solvation force is strongly repulsive for narrow pores and attractive for wide pores. In the presence of adsorbed fluid both parts of the curve of the solvation force may develop oscillatory behavior dependent on the density of pillars, the number of segments and adsorption conditions. Also, the size ratio between adsorbed fluid species and chain segments is of importance for the development of oscillations. The choice of these parameters is crucial for efficient manipulation of the solvation force as desired for pores of different width.